PENGARUH KAPASITAS OPERASI, PERTUMBUHAN PENJUALAN DAN ARUS KAS TERHADAP FINANCIAL DISTRESS - Jesih, Jesih; Wizanasari, Wizanasari (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2023)
This study aims to analyze how much influence operating capacity, sales growth and cash flow have on financial distress in processed foods sub-sector companies listed on the Indonesia Stock Exchange in 2017 - 2021. The independent variables of this study are operating capacity, sales growth and cash flow and the dependent variable in this study, namely financial distress. This type of research is descriptive with a quantitative approach. The sampling technique in this study used purposive sampling. Data collection techniques in this study are secondary data with data collection methods, namely documentation. The research obtained as many as 12 companies, where the research was conducted for 5 years which obtained as many as 60 observations. Of the 60 observations that will be tested, 50 companies are due to the outlier test results. Data management in this study uses the eviews 9 application. The results of the study show that operating capacity and cash flow have an influence on financial distress, while sales growth has no effect on financial distress. This study also shows that operating capacity, sales growth and cash flow simultaneously influence financial distress.